Identification of fast-changing signals by means of adaptive chaotic transformations - Berezowski, Marek; Lawnik, Marcin (Nonlinear Analysis: Modelling and Control, 2014)
The adaptive approach of strongly non-linear fast-changing signals identification is discussed. The approach is devised by adaptive sampling based on chaotic mapping “in yourself” of a signal. Presented sampling way may be utilized online in the automatic control of chemical reactor (throughout identification of concentrations and temperature oscillations in real-time), in medicine (throughout identification of ECG and EEG signals in real-time), etc. In this paper, we presented it to identify the Weierstrass function and ECG signal.